Toponymy Can Be Alive - Rozhansky, Mikhail (project baikal, 2015)
The author thinks that any discussion on the historical restoration of toponyms in Irkutsk is unpromising and offers to treat toponyms as a resource for vitalizing the city space. This could be a priority approach to the problems of city toponymy.
Keywords: toponymy; city space; Irkutsk; historical memory; pragmatics